PEDOT electromagnetic shielding polymer film, preparation method and application
By using the polymerization reaction of EDOT monomer and iron salt oxidizer in PEDOT electromagnetic shielding materials, combined with appropriate additives, a high conductivity and low resistance PEDOT electromagnetic shielding polymer film is prepared, which solves the problem of low conductivity and high cost of existing materials. The problem of this problem has achieved efficient electromagnetic shielding effect and good flexibility.
Patent Information
- Application Number
- CN202411656919.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-07
AI Technical Summary
The existing PEDOT electromagnetic shielding materials have low conductivity, high cost and limited flexibility, making it difficult to achieve efficient electromagnetic shielding effects.
A polymerization reaction method containing EDOT monomer and iron salt oxidizer was adopted to regulate the reaction conditions by additives such as PVA, PVP and starch, and PEDOT electromagnetic shielded polymer film with low surface resistance and high conductivity was prepared.
The obtained PEDOT electromagnetic shielding polymer film surface resistance is 1~3Ω/sq, the conductivity can reach 2000 S/cm, the electromagnetic shielding efficiency reaches more than 40dB, and the cost is low. It is suitable for surface installation of devices of different shapes, with acid and alkali resistance and Antioxidant properties.
Smart Images

Figure CN119264489A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new materials, and in particular relates to a PEDOT electromagnetic shielding polymer film, a preparation method and an application thereof. Background Art
[0002] With the rapid development of science and technology, electronic devices are everywhere in our lives, and the problem of electromagnetic radiation is becoming increasingly prominent. The research and development and application of flexible conductive polymer shielding materials have great research significance.
[0003] At present, electromagnetic shielding materials are mainly metal materials or composite materials. Compared with pure metal materials, they have the advantages of light weight, high strength, high durability, simple processability and high flexibility. Generally, non-conductive polymers such as polyvinyl alcohol, polyvinylidene fluoride, polylactic acid, polyurethane, polyethyleneimine, etc. are mixed with various conductive fillers to achieve conductivity and give them electromagnetic shielding function. These conductive fillers can be metal nanoparticles, metal nanofibers, metal nanowires, graphene, graphene oxide, carbon nanotubes and metal organic framework compounds, etc., and finally obtain conductive filler reinforced polymer nanocomposites with light weight and excellent shielding efficiency, which can be used to shield electromagnetic interference. However, these technologies not only have expensive raw materials, but also complex operations, high production costs, and greatly limited flexibility. Therefore, using highly flexible and highly conductive polymers for one-time molding is an effective way to overcome the above shortcomings.
[0004] Poly(3,4-ethylenedioxythiophene) (PEDOT) is a conductive polymer with the second highest conductivity after polyacetylene. Compared with polyacetylene, PEDOT has the characteristics of low cost, high flexibility and good environmental stability. It is the most promising high-performance electromagnetic shielding conductive flexible material. So far, a large number of domestic and foreign scholars have applied PEDOT to the field of electromagnetic shielding. Professor Min Douyong's research group, Sharma et al., Professor Ghaderi's research group, Professor Zhang Xiwen's research group, Taj et al. have successively used PEDOT to prepare electromagnetic shielding composite materials. However, these are all composite materials prepared by using PEDOT as filler, or composite materials prepared by mixing highly conductive metal particles with PEDOT:PSS. The common characteristics are that the film is thicker, the flexibility is relatively low, the cost is higher, and it is not easy to chemically process. The real electromagnetic shielding material made of pure PEDOT comes from Bora et al. They used commercial PEDOT:PSS to directly prepare a flexible electromagnetic shielding film with an electromagnetic shielding efficiency of 40 dB. The film thickness is 9μm and the conductivity is only 769 S / cm. However, since the film uses commercial PEDOT:PSS, its cost is relatively high and its conductivity is relatively low.
[0005] Patent application publication number CN106297968A discloses a high-thickness and high-conductivity PEDOT film and a preparation method thereof, using EDOT monomer as a raw material, using highly alcohol-soluble iron salt FeX3 containing weakly basic anions as an oxidant, and then directly preparing a PEDOT film composed of PEDOT:X by a gas phase method or a solution method, wherein X is a highly alcohol-soluble weakly basic anion, preferably at least one of camphorsulfonate ions, long-chain alkylbenzenesulfonate ions, alkylnaphthalenesulfonate ions, dialkylnaphthalenesulfonate ions and dinonylnaphthalene disulfonate ions. It utilizes the high alcohol solubility of the precursor iron salt oxidant solution to increase the concentration and viscosity of the spin-coating solution, inhibit the crystallization of the oxidant during the reaction, and does not need to add copolymer anti-crystallization inhibitors (pyridine, PEPG, etc.), thereby obtaining a high-thickness PEDOT film. Secondly, the weakly alkaline anions in the iron salt oxidant can be used to combine with the ions produced during the reaction to regulate the actual concentration of hydrogen ions and trivalent iron ions, thereby controlling the reaction rate. The surface resistance of the obtained PEDOT film is 8Ω / sq and the conductivity is 1000 S / cm. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a PEDOT electromagnetic shielding polymer film, a preparation method and an application thereof. The PEDOT electromagnetic shielding polymer film has a higher density and a lower resistance, and can improve the electromagnetic shielding effect.
[0007] The embodiment of the present invention provides a method for preparing a PEDOT electromagnetic shielding polymer film, wherein a substrate coated with an oxidant solution is subjected to a polymerization reaction in a vapor containing an EDOT monomer, and then the oxidant is removed and the film is dried to obtain the PEDOT electromagnetic shielding polymer film; the oxidant solution comprises an iron salt, an additive and water, and the additive is one or more of polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), starch, polyethylene glycol (PEG), and polyoxypropylene polyoxyethylene copolymer (PEG-PPG-PEG).
[0008] Preferably, the iron salt is ferric chloride, ferric trifluoromethanesulfonate, ferric p-toluenesulfonate or ferric bromide.
[0009] Preferably, the iron salt is ferric chloride.
[0010] Preferably, the additive is polyvinyl alcohol.
[0011] Preferably, in the oxidant solution, the mass concentration of iron salt is 20-50%, preferably 30-40%.
[0012] Preferably, in the oxidant solution, the mass concentration of the additive is 4-15%, preferably 4.8-6%.
[0013] Preferably, the polymerization reaction temperature is 100-150° C., and the polymerization reaction time is preferably 60-180 min.
[0014] Preferably, the oxidant is removed by immersing in a solution, preferably water, for more than 5 days, preferably 7 days, to remove iron salts and additives.
[0015] Preferably, the drying temperature is 70-90°C, preferably 80°C.
[0016] The embodiment of the present invention provides a PEDOT electromagnetic shielding polymer film, which is prepared by adopting the preparation method.
[0017] An embodiment of the present invention provides an application of the PEDOT electromagnetic shielding polymer film, and the PEDOT electromagnetic shielding polymer film is used for preparing an electromagnetic shielding device.
[0018] The substrate of the present invention can be any substrate that can carry an oxidant solution, such as a flexible glass sheet or polyimide. The polymerization reaction of the present invention can be carried out in a reaction furnace containing EDOT monomer vapor.
[0019] The beneficial effects of the present invention are that the PEDOT electromagnetic shielding polymer film obtained by the present invention has a surface resistance of 1 to 3Ω / sq, a thickness of 1 to 20 μm, a conductivity of up to 2000 S / cm, an electromagnetic shielding effectiveness of more than 40 dB, and can be used in electromagnetic shielding devices.
[0020] The solvent used throughout the present invention is water, and no organic solvent is used in the process, which is green and environmentally friendly. The raw materials used in the present invention are iron salts, such as ferric chloride, additives, such as PVA, and EDOT monomers, which are low in cost and good in effect. The conductive polymer synthesized by the present invention has a layered molecular arrangement structure, which is of great help in improving the electromagnetic shielding effectiveness. The film provided by the present invention is not only light in weight, but also more flexible, and can be suitable for installation on the surfaces of devices of different shapes. The film of the present invention has the characteristics of acid and alkali resistance, good oxidation resistance, etc., and can be suitable for applications in special environments. The preparation method of the process of the present invention has the advantages of simplicity, high efficiency, low equipment requirements, wide application range, environmental friendliness and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the relationship between the surface resistance of PEDOT film and the electromagnetic shielding effect (SE).
[0022] Figure 2 The effect of different additives on the surface resistance of PEDOT film.
[0023] Figure 3The effect of the concentration of PVA aqueous solution on the surface resistance of PEDOT film.
[0024] Figure 4 The effect of ferric chloride concentration on the surface resistance of PEDOT film.
[0025] Figure 5 This is the effect of polymer reaction time on the surface resistance of PEDOT film.
[0026] Figure 6 This is the effect of polymer reaction time on the surface resistance of PEDOT film.
[0027] Figure 7 Infrared spectra of oxidant film and PEDOT film.
[0028] Figure 8 This is a physical picture of the PEDOT film. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0030] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0031] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0032] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0033] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0034] Example 1 PVA was dissolved in deionized water to prepare an aqueous solution with a mass concentration of 8 wt%, and solid ferric chloride hexahydrate was dissolved in the PVA aqueous solution to prepare an oxidant solution with a concentration of 40 wt% for later use (i.e., the oxidant solution, the mass concentration of ferric chloride was 40%, and the mass concentration of PVA was 4.8%).
[0035] A 10 cm*10 cm polyimide film (thickness of 100 μm) was spread flat on a glass plate, and the oxidant solution was scraped onto the polyimide film using a scraper to form a uniform oxidant solution film.
[0036] The oxidant solution film was transferred to a reactor containing EDOT monomer vapor for polymerization reaction at a temperature of 130 °C and a polymerization reaction time of 180 min. After the reaction was completed, the composite film was soaked in deionized water for 7 days to remove the unreacted ferric chloride and additives. Finally, the soaked film was dried in a blast oven at 80 °C to obtain a PEDOT composite conductive film.
[0037] Example 2 PVA was dissolved in deionized water to prepare an aqueous solution with a mass concentration of 10 wt%, and solid ferric chloride hexahydrate was dissolved in the PVA aqueous solution to prepare an oxidant solution with a concentration of 40 wt% for later use (i.e., the oxidant solution, the mass concentration of ferric chloride was 40%, and the mass concentration of PVA was 6%).
[0038] A 10 cm*10 cm polyimide film (thickness of 100 μm) was spread flat on a glass plate, and the oxidant solution was scraped onto the polyimide film using a scraper to form a uniform oxidant solution film.
[0039] The oxidant solution film was transferred to a reactor containing EDOT monomer vapor for polymerization reaction. The polymerization temperature was 130 °C and the polymerization time was 180 min. After the reaction was completed, the composite film was soaked in deionized water for 7 days to remove the unreacted ferric chloride and additives. Finally, the soaked film was dried in a blast oven at 80 °C to obtain a PEDOT composite conductive film.
[0040] Example 3 PVA was dissolved in deionized water to prepare an aqueous solution with a mass concentration of 8 wt%, and solid ferric chloride hexahydrate was dissolved in the PVA aqueous solution to prepare an oxidant solution with a concentration of 30 wt% for later use (i.e., the oxidant solution, the mass concentration of ferric chloride was 30%, and the mass concentration of PVA was 5.6%).
[0041] A 10 cm*10 cm polyimide film (thickness of 100 μm) was spread flat on a glass plate, and the oxidant solution was scraped onto the polyimide film using a scraper to form a uniform oxidant solution film.
[0042] The oxidant solution film was transferred to a reactor containing EDOT monomer vapor for polymerization reaction. The polymerization temperature was 130 °C and the polymerization time was 180 min. After the reaction was completed, the composite film was soaked in deionized water for 7 days to remove the unreacted ferric chloride and additives. Finally, the soaked film was dried in a blast oven at 80 °C to obtain a PEDOT composite conductive film.
[0043] Example 4 PVA was dissolved in deionized water to prepare an aqueous solution with a mass concentration of 8 wt %, and solid ferric chloride hexahydrate was dissolved in the PVA aqueous solution to prepare an oxidant solution with a concentration of 40 wt %, which was set aside.
[0044] A 10 cm*10 cm glass sheet (thickness of 200 μm) was spread flat on a glass plate, and the oxidant solution was scraped onto the glass sheet with a scraper to form a uniform oxidant solution film.
[0045] The oxidant solution film was transferred to a reactor containing EDOT monomer vapor for polymerization reaction. The polymerization temperature was 130 °C and the polymerization time was 180 min. After the reaction was completed, the composite film was soaked in deionized water for 7 days to remove the unreacted ferric chloride and additives. Finally, the soaked film was dried in a blast oven at 80 °C to obtain a PEDOT composite conductive film.
[0046] Example 5 PVA was dissolved in deionized water to prepare an aqueous solution with a mass concentration of 8 wt %, and solid ferric chloride hexahydrate was dissolved in the PVA aqueous solution to prepare an oxidant solution with a concentration of 40 wt %, which was set aside.
[0047] A 10 cm*10 cm polyimide film (thickness of 100 μm) was spread flat on a glass plate, and the oxidant solution was scraped onto the polyimide film using a scraper to form a uniform oxidant solution film.
[0048] The oxidant solution film was transferred to a reactor containing EDOT monomer vapor for polymerization reaction. The polymerization temperature was 120 °C and the polymerization time was 180 min. After the reaction was completed, the composite film was soaked in deionized water for 7 days to remove the unreacted ferric chloride and additives. Finally, the soaked film was dried in a blast oven at 80 °C to obtain a PEDOT composite conductive film.
[0049] Example 6 PVP was dissolved in deionized water to prepare an aqueous solution with a mass concentration of 8 wt %, and solid ferric chloride hexahydrate was dissolved in the PVP aqueous solution to prepare an oxidant solution with a concentration of 40 wt % for later use.
[0050] A 10 cm*10 cm polyimide film (thickness of 100 μm) was spread flat on a glass plate, and the oxidant solution was scraped onto the polyimide film using a scraper to form a uniform oxidant solution film.
[0051] The oxidant solution film was transferred to a reactor containing EDOT monomer vapor for polymerization reaction. The polymerization temperature was 130 °C and the polymerization time was 150 min. After the reaction was completed, the composite film was soaked in deionized water for 7 days to remove the unreacted ferric chloride and additives. Finally, the soaked film was dried in a blast oven at 80 °C. A PEDOT composite conductive film was obtained.
[0052] Example 7 Starch was dissolved in deionized water to prepare an aqueous solution with a mass concentration of 8 wt %, and solid ferric chloride hexahydrate was dissolved in the starch aqueous solution to prepare an oxidant solution with a concentration of 40 wt % for later use.
[0053] A 10 cm*10 cm polyimide film (thickness of 100 μm) was spread flat on a glass plate, and the oxidant solution was scraped onto the polyimide film using a scraper to form a uniform oxidant solution film.
[0054] The oxidant solution film was transferred to a reactor containing EDOT monomer vapor for polymerization reaction. The polymerization temperature was 130 °C and the polymerization time was 180 min. After the reaction was completed, the composite film was soaked in deionized water for 7 days to remove the unreacted ferric chloride and additives. Finally, the soaked film was dried in a blast oven at 80 °C to obtain a PEDOT composite conductive film.
[0055] Comparative Example 1 The solid ferric chloride hexahydrate is dissolved in the aqueous solution to prepare an oxidant solution with a concentration of 40 wt % for later use.
[0056] A 10 cm*10 cm polyimide film (thickness of 100 μm) was spread flat on a glass plate, and the oxidant solution was scraped onto the polyimide film using a scraper to form an oxidant solution film.
[0057] The oxidant solution film was transferred to a reactor containing EDOT monomer vapor for polymerization reaction. The polymerization temperature was 130 °C and the polymerization time was 180 min. After the reaction was completed, the composite film was soaked in deionized water for 7 days to remove the unreacted ferric chloride. Finally, the soaked film was dried in a blast oven at 80 °C to obtain a composite film.
[0058] Comparative Example 2 PVA was dissolved in deionized water to prepare an aqueous solution with a mass concentration of 8 wt%, and solid ferric chloride hexahydrate was dissolved in the PVA aqueous solution to prepare an oxidant solution with a concentration of 10 wt% for later use (i.e., the oxidant solution, the mass concentration of ferric chloride was 10%, and the mass concentration of PVA was 7.2%).
[0059] A 10 cm*10 cm polyimide film (thickness of 100 μm) was spread flat on a glass plate, and the oxidant solution was scraped onto the polyimide film using a scraper to form a uniform oxidant solution film.
[0060] The oxidant solution film was transferred to a reactor containing EDOT monomer vapor for polymerization reaction. The polymerization temperature was 130 °C and the polymerization time was 180 min. After the reaction was completed, the composite film was soaked in deionized water for 7 days to remove the unreacted ferric chloride and additives. Finally, the soaked film was dried in a blast oven at 80 °C to obtain a PEDOT composite conductive film.
[0061] Comparative Example 3 PVA was dissolved in deionized water to prepare an aqueous solution with a mass concentration of 8 wt %, and solid ferric chloride hexahydrate was dissolved in the PVA aqueous solution to prepare an oxidant solution with a concentration of 40 wt %, which was set aside.
[0062] A 10 cm*10 cm polyimide film (thickness of 100 μm) was spread flat on a glass plate, and the oxidant solution was scraped onto the polyimide film using a scraper to form a uniform oxidant solution film.
[0063] The oxidant solution film was transferred to a reactor containing EDOT monomer vapor for polymerization reaction. The polymerization temperature was 60 °C and the polymerization time was 180 min. After the reaction was completed, the composite film was soaked in deionized water for 7 days to remove the unreacted ferric chloride and additives. Finally, the soaked film was dried in a blast oven at 80 °C. A PEDOT composite conductive film was obtained.
[0064] Comparative Example 4 PVA was dissolved in deionized water to prepare an aqueous solution with a mass concentration of 8 wt %, and solid ferric chloride hexahydrate was dissolved in the PVA aqueous solution to prepare an oxidant solution with a concentration of 40 wt %, which was set aside.
[0065] A 10 cm*10 cm polyimide film (thickness of 100 μm) was spread flat on a glass plate, and the oxidant solution was scraped onto the polyimide film using a scraper to form a uniform oxidant solution film.
[0066] The oxidant solution film was transferred to a reactor containing EDOT monomer vapor for polymerization reaction. The polymerization temperature was 80 °C and the polymerization time was 180 min. After the reaction was completed, the composite film was soaked in deionized water for 7 days to remove the unreacted ferric chloride and additives. Finally, the soaked film was dried in a blast oven at 80 °C. A PEDOT composite conductive film was obtained.
[0067] Comparative Example 5 Glycerol was dissolved in deionized water to prepare an aqueous solution with a mass concentration of 8 wt %, and solid ferric chloride hexahydrate was dissolved in the glycerol aqueous solution to prepare an oxidant solution with a concentration of 40 wt % for later use.
[0068] A 10 cm*10 cm polyimide film (thickness of 100 μm) was spread flat on a glass plate, and the oxidant solution was scraped onto the polyimide film using a scraper to form a uniform oxidant solution film.
[0069] The oxidant solution film was transferred to a reactor containing EDOT monomer vapor for polymerization reaction. The polymerization temperature was 130°C and the polymerization time was 180 min. After the reaction was completed, the composite film was soaked in deionized water for 7 days to remove the unreacted ferric chloride and additives. Finally, the soaked film was dried in a blast oven at 80°C to obtain a PEDOT composite conductive film.
[0070] The relationship between the surface resistance of the PEDOT film obtained in Example 1 and the electromagnetic shielding effect (SE) is as follows: Figure 1 As shown, as the surface resistance of the film decreases, the electromagnetic shielding effect of the film becomes better. When the surface resistance of the film is less than 2 Ω / sq, the electromagnetic shielding effect can reach more than 40 dB. Therefore, obtaining a low-resistance PEDOT polymer film is the key to the present invention.
[0071] On the basis of Example 1, PVA was replaced by the other five additives, and the other steps were the same as in Example 1. The surface resistance of the films obtained with different additives was compared. The experimental results are shown in Figure 2As shown, the inventors selected five additives with a large number of hydroxyl groups (-OH) in their molecular structures as comparison. The experimental results show that when the additives are PVA, PVP and starch, the surface resistances obtained can reach 2 Ω / sq, 6 Ω / sq and 7 Ω / sq respectively, so they all have a high electromagnetic shielding effect. The additives are glycerol (i.e. comparative example 5), sodium polyoxyethylene fatty alcohol ether sulfate (AES), and PEG-PPG-PEG. Although these three additives contain a large number of hydroxyl groups, their effects are far inferior to the aforementioned three additives. In general, PVA has the best effect among these six additives.
[0072] Based on Example 1, the concentration of PVA in the PVA aqueous solution was changed (the concentration of PVA in the PVA aqueous solution in Example 1 was 8%), and the other contents were the same as in Example 1.
[0073] The effect of the concentration of PVA aqueous solution on the surface resistance of PEDOT film was tested. The results are as follows: Figure 3 As shown in the figure, when the PVA concentration is 0 wt% (i.e., comparative example 1), the surface resistance of the PEDOT film has exceeded 100 Ω / sq. In fact, in actual operation, it is difficult for the oxidant solution without PVA to be evenly coated on the polyimide film or glass plate. Therefore, only a limited area can be obtained instead of a complete PEDOT film. When an appropriate amount of PVA additive is added, not only a complete PEDOT film can be obtained, but also the film resistance will be lower. Finally, when the PVA concentration exceeds 8 wt%, the film surface resistance can reach below 2 Ω / sq.
[0074] Based on Example 1, the concentration of ferric chloride in the oxidant solution was changed (the concentration of ferric chloride in the oxidant solution in Example 1 was 40%), and the other contents were the same as Example 1.
[0075] The effect of ferric chloride concentration on the surface resistance of PEDOT film was tested. The test results are as follows: Figure 4 As shown, Figure 4 The effect of the concentration of ferric chloride on the surface resistance of the PEDOT film is shown. When the concentration of ferric chloride is too low, such as 10 wt% (i.e., Comparative Example 2), the surface resistance will be too high, and when the concentration of ferric chloride reaches 20 wt%, the surface resistance will drop sharply. Finally, when the concentration of the oxidant reaches 40 wt%, the surface resistance can reach the corresponding 2 Ω / sq or less. This is because too little ferric chloride will cause the additive to not be completely oxidized, which will further lead to incomplete synthesis of the PEDOT film, more defects, and thus reduce its conductivity.
[0076] Based on Example 1, the polymerization reaction time was changed, and the other contents were the same as Example 1.
[0077] The effect of polymerization reaction time on the surface resistance of PEDOT film was tested. The test results are as follows: Figure 5 As shown, Figure 5 The effect of polymerization reaction time on the surface resistance of PEDOT film is shown. When the polymerization reaction time is too short, the oxidant and additive cannot fully react, which will cause defects in the PEDOT film and reduce its conductivity. Figure 5 It can be seen that when the synthesis time exceeds 60 min, the surface resistance decreases sharply and reaches below 10 Ω / sq. Finally, when the synthesis time reaches 3 hours, the surface resistance can reach below 2 Ω / sq.
[0078] Based on Example 1, the polymerization reaction temperature was changed, and the other contents were the same as Example 1.
[0079] The effect of polymerization reaction temperature on the surface resistance of PEDOT film was tested. The test results are as follows: Figure 6 As shown, Figure 6 The effect of polymerization reaction temperature on the surface resistance of PEDOT film is shown. When the polymerization reaction temperature is too low, such as 60 ℃ (i.e., Comparative Example 3), the obtained PEDOT film is not conductive. In fact, we use a polymerization reaction temperature in the range of 60~150 ℃ and find that when the polymerization reaction temperature is less than 100 ℃, the obtained PEDOT film is not conductive. When the temperature reaches and exceeds 100 ℃, the surface resistance of PEDOT decreases sharply. When the temperature is 130 ℃, the PEDOT film with the best conductivity (surface resistance less than 2 Ω / sq) is obtained.
[0080] In order to investigate or prove the role of PVA in the polymerization reaction, we use infrared characterization methods, such as Figure 7 As shown, the four curves represent the infrared spectra of four samples: a PVA aqueous solution with a concentration of 4.8 wt% is applied to a polyimide film and dried to obtain a sample, which is recorded as sample (1); the oxidant solution described in Example 1 is applied to a polyimide film and heated at 60°C for 180 min to obtain a sample, which is recorded as sample (2); the oxidant solution described in Example 1 is applied to a polyimide film and heated at 130°C for 180 min to obtain a sample, which is recorded as sample (3); the PEDOT composite conductive film obtained in Example 1 is recorded as sample (4). Samples (1), (2), (3) and (4) were characterized by infrared spectrometer, respectively, and the following results were obtained: Figure 7 Infrared spectrum of .
[0081] like Figure 7 Infrared spectrum of sample (2) in Figure 1. When the temperature is 60°C, the oxidant film has a wavelength of 1750 cm -1 There is no absorption peak at 3300 cm-1 The narrow absorption peak of the hydroxyl group is consistent with the same wavelength position in the PVA spectrum of sample (1), which indicates that the temperature is too low to oxidize PVA. When the temperature is 130°C, as shown in the infrared spectrum of sample (3), at 1750 cm -1 There is an obvious -C=O absorption peak, and the 3300 cm -1 The hydroxyl absorption peak of PVA is significantly broadened. In addition, a peak consistent with that of sample (3) appears at the same wavelength in the PEDOT film, which indicates that the hydroxyl group of PVA is successfully oxidized to carboxylic acid at 130°C. This also indicates that a higher temperature is required to successfully synthesize high-quality PEDOT films.
[0082] This is because the hydroxyl functional groups of the additives can be oxidized to carboxylic acids (-C=O, 1750 cm -1 ), carboxylic acid can provide a large number of protons, which is the key to the synthesis of PEDOT. PVA, starch and PVP are polyhydroxy substances that are relatively easy to oxidize, while AES, PEG-PPG-PEG and glycerol are relatively stable and difficult to be oxidized. Therefore, the effect is not as good as the first three.
[0083] Figure 8 This is a real picture of the PEDOT film of Example 1. When the film is facing the fluorescent lamp and observed, it can be seen that light cannot penetrate the PEDOT film, which shows that the PEDOT film has a high degree of density.
[0084] A person skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of protection of the present application is limited to these examples. In line with the concept of the present application, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of different aspects of one or more embodiments of the present application as described above, which are not provided in detail for the sake of simplicity.
[0085] One or more embodiments of the present application are intended to cover all such substitutions, modifications and variations that fall within the broad scope of the present application. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of one or more embodiments of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a PEDOT electromagnetic shielding polymer film, characterized in that: The substrate coated with an oxidant solution is subjected to a polymerization reaction in a vapor containing EDOT monomer, and then the oxidant is removed and dried to obtain a PEDOT electromagnetic shielding polymer film; the oxidant solution includes iron salt, additives and water, and the additive is one or more of polyvinyl alcohol, polyvinyl pyrrolidone, starch, polyethylene glycol, and polyoxypropylene-polyoxyethylene copolymer.
2. The preparation method according to claim 1, characterized in that: The iron salt is ferric chloride, ferric trifluoromethanesulfonate, ferric p-toluenesulfonate or ferric bromide.
3. The preparation method according to claim 2, characterized in that: The iron salt is ferric chloride.
4. The preparation method according to claim 1, characterized in that: The additive is polyvinyl alcohol.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In the oxidant solution, the mass concentration of iron salt is 20-50%.
6. The preparation method according to any one of claims 1 to 4, characterized in that: In the oxidant solution, the mass concentration of the additive is 4-15%.
7. The preparation method according to any one of claims 1 to 4, characterized in that: The polymerization temperature is 100-150°C.
8. The preparation method according to any one of claims 1 to 4, characterized in that: The oxidant is removed by immersion in a solution.
9. A PEDOT electromagnetic shielding polymer film, characterized in that: The method is described in any one of claims 1 to 8.
10. An application of the PEDOT electromagnetic shielding polymer film as claimed in claim 9, characterized in that: The PEDOT electromagnetic shielding polymer film is used for preparing electromagnetic shielding devices.
Citation Information
Patent Citations
High-thickness and high-conductivity PEDOT film and preparation method thereof
CN106297968A
Cited By
Active cable with high environmental affinity and preparation method thereof
CN120413171A
PEDOT: PSS nanoparticles, and preparation method and application thereof
CN121227104A